1995
DOI: 10.1002/pi.1995.210380101
|View full text |Cite
|
Sign up to set email alerts
|

Studies on permeation through polymer latex films, I. Films containing no or only low levels of additives

Abstract: A range of permeation techniques were employed to investigate the transport mechanisms across polymer films cast from lattices containing either no or only low levels of water soluble leachates such as residual surfactant from polymerisation or added plasticiser essential to film formation. Hydrophilic pathways can provide a mechanism of transport, in addition to partition into and solution‐diffusion in the polymer phase. Loss of porosity by low Tg polymers on drying highlights the value of solute probes in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Examples of pore forming agents tested include small molecule additives (e.g., urea, glycerol, glucose, sucrose, etc.) [ 34 , 35 , 36 , 37 , 38 , 39 ] and water-soluble polymers (WSPs) (e.g., polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG), etc.) [ 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of pore forming agents tested include small molecule additives (e.g., urea, glycerol, glucose, sucrose, etc.) [ 34 , 35 , 36 , 37 , 38 , 39 ] and water-soluble polymers (WSPs) (e.g., polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG), etc.) [ 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polymer particle coalescence and therefore the permeability can be difficult to control during drying of a coating. During drying the fusion of latex spheres is driven by polymer−water interfacial tension, capillary pressure, layer compression, and interparticle adhesion (9−13). Even after the coating has dried, further reduction in permeability can occur as a function of time, relative humidity, and temperature (12, 13).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of drug release from Eudragit RL and RS-based drug delivery systems has been proposed to take place through the control of fluid permeation and consequent dissolution and diffusion of the drug (41,42). It has been shown that drug diffusion is pH independent, which can be explained by the ionisation of the quaternary ammonium groups of the polymers at all pH levels with the gastrointestinal tract.…”
Section: Resultsmentioning
confidence: 99%